Restructuring the Schoolbook Provision System in Indonesia - Supriadi, Dedi (Education Policy Analysis Archives, 1999)
Schoolbooks account for between 65% and 75% of all publishing activity in Indonesia. The amount of money allocated is continually increasing. Priority is given to the primary and junior secondary school levels (6+3 years), which are compulsory. Between 1969 and 1988, the Government of Indonesia (GOI) has produced some 550 million primary textbooks and library books. Up to the year 2000, the GOI has decided to allocate the total of US 355.2 million to produce 250 million copies of primary and junior secondary school textbooks to reach the ratio of one book for each student. In addition, around Rp 20-50 billion (US 10-20 million) annually is spent to purchase 8-17 million copies of reading books which are aimed at stimulating the reading interest of primary school children. These books are distributed free to some 168,000 primary and 26,969 junior secondary schools throughout Indonesia. Following the massive efforts to increase book availability at schools, some innovative policies are being taken. Book evaluation standards have been improved to ensure that only high quality books are used at schools. The distribution system has been restructured to guarantee that books reach targeted schools. Consequently, the book monitoring system has had to be strengthened to examine whether or not the books really reach the schools and are used properly by students and teachers in the classrooms. In the last three years, there has also been a growing concern with multicultural issues in schoolbook provision programs. In such a culturally diverse nation as Indonesia, schoolbooks should also be culturally sensitive and be recognize the varied sociocultural backgrounds which affect students' learning.